A systematic study on the discrepancy of fluorescence properties between in solutions and in cells: super-bright, environment-insensitive benzocoumarin dyes. Issue 72 (12th August 2020) - Reo, Ye Jin; Jun, Yong Woong; Cho, Seo Won; Jeon, Jinseong; Roh, Hajung; Singha, Subhankar; Dai, Mingchong; Sarkar, Sourav; Kim, Hye Rim; Kim, Sojeong; Jin, Yusung; Jung, Yun Lim; et al.
Abstract : The benzocoumarins show distinctive emission behaviour from some commonly-used dyes in organic, aqueous buffer, and cellular media, which compels us to recognize the cellular environment as the third space for fluorophores. Abstract : The benzocoumarin dyes fluoresce negligibly in aqueous media but very strongly in cells, whereas representative conventional dyes display contrasting behaviour; the distinct emission behaviour of the fluorophores in organic solutions, in aqueous media, and in cell convinces the uniqueness of the cellular environment. The in cellulo superbright benzocoumarins also reveal an environment-insensitive emission behaviour, which is required for the reliable analysis via ratiometric imaging.